Design and analysis of an inertial-piezoelectric drive - Muhammad Nazir Mohamed Khamal. (2011)
Miniaturisation in the last decades is researching into tools that can manipulate position micro-parts accurately and at large working range. A new technology referred to stick-slip actuators or inertial drive has been used for positioning in micro-manipulators. The inertial drive under this project is a prototype that is constructed in order to study the stick-slip phenomenon in a friction driven system. Firstly, a mathematical model is established and experimentally verified for one degree of freedom. In addition, investigations on how to improve the motion characteristics are carried out by proposing measures to reduce unwanted vibrations or errors. The influence of friction between the load and inertial mass on the drive‟s performance is examined and modelled based on the Stribeck friction. Lastly distinct mode shapes can be produced depending on the external force and relative velocity of two masses.